Green governance and the EKC hypothesis: Evidence from Vietnamese provinces - Hoang, Trieu-Hoa; Le, Ba-Tam; Mai, Thi-Thanh-Xuan; Pham, Thi-Linh (Edelweiss Applied Science and Technology, 2024)
The Environmental Kuznets Curve (EKC) posits an inverted U-shaped relationship between environmental degradation and economic development, suggesting that while economic growth may initially harm the environment, it can ultimately lead to both economic and environmental benefits in the long run. Empirical evidence of this hypothesis strongly supports the Sustainable Development Goals (SDGs) such as SDG 1 (No Poverty), SDG 8 (Good Jobs and Economic Growth), and SDG 11 (Sustainable Cities and Communities). While the EKC literature focused more on national or cross-country analyses, limited studies examined this hypothesis at the regional or provincial level and often used data from the U.S. and China. This study revisits the EKC hypothesis in Vietnamese provinces by examining municipal solid waste (MSW), which is important to the SDGs but has attracted less attention compared to other pollutants. The role of green governance, measured via the provincial green index (PGI), is also examined. Findings indicate that the EKC exists at the provincial level in Vietnam, with the PGI reducing the GDP requirement for the EKC turning point, thereby accelerating environmental improvements. Consequently, promoting green governance is important for emerging countries such as Vietnam to achieve sustainable development and the SDGs.